A blueprint for overcoming barriers to the use of nature-based coastal protection in Australia - Morris, Rebecca L.; Pomeroy, Andrew W. M.; Boxshall, Anthony; Colleter, Gildas; Dack, David; Dunlop, Andrew R.; Hanslow, David; King, Sam; Magini, Ariana; O’Malley-Jones, Katrina; Sultmann, Sel; Townsend, Murray; et al. (Frontiers in Environmental Science, 2024)
The global loss of coastal habitats is putting communities at risk of erosion and flooding, as well as impacting ecosystem function, cultural values, biodiversity, and other services. Coastal habitat restoration can provide a nature-based solution to the increasing need for climate adaptation on the coast while recovering lost ecosystems. Despite the benefits of using nature-based coastal protection to manage coastal hazards, there are scientific, socio-political and economic barriers to the broad use of this approach. Understanding the details of these barriers from the perspective of multiple stakeholders is essential to identifying solutions to overcome them. Using a workshop with participants that are key partners and stakeholders (from government, engineering consulting firms, and non-governmental organisations) in the management, design, and delivery of a coastal protection solution we aimed to: (1) gain a better understanding of the barriers faced by multiple stakeholders involved in the implementation of nature-based coastal protection; and (2) identify tangible solutions to these barriers to increase or support implementation, help focus attention on areas for future research, and inform pathways forward for the governance of nature-based coastal protection. We defined 19 barriers to nature-based coastal protection, but the primary ones that are experienced during the delivery of a project are a lack of: education and awareness; community support; necessary expertise and technical guidance; and uncertainty around: the risk reduction that can be achieved; planning and regulatory processes; and ownership of the structure. Two barriers that do not persist during the design stages of a project but are overarching as to whether nature-based coastal protection is considered in the first place, are government support and the availability of funding. The importance of these primary barriers changes depending on the method of nature-based coastal protection. We conclude by identifying both immediate actions and long-term solutions for enabling nature-based coastal protection in response to each of the primary barriers.